Theological resources for building resilience to gangster identity formations. A study of the Cape Flats - Vorster, Nico (Stellenbosch Theological Journal, 2018)
This essay probes the remedial promise of Christian narratives on resilience in creating buffers against gangster identity formation on the Cape Flats. First, we consult and compare both quantitative and qualitative psychosocial studies on the causes of gangster identity formation on the Cape Flats. Thereafter, we discuss the dominant Christian narratives on resilience and examine their applicability and remedial potential for the specific social setting. The essay finds that the social settings within which gangster identities are formed determine to a large degree the kind of resilience competencies that have to be instilled in individuals and communities, as well as the type of theological discourse that ought to be followed. A certain type of theological discourse on resilience might be helpful in creating buffers against gangster identity formation within some communities of the Cape Flats, but the same narrative could yield negative results in others. The type of theological approach followed should therefore be closely aligned to the audience addressed to ensure that the competencies instilled in communities do not, in fact, grow into risk factors.